M³-m-am²+a x²+4yz-xy-4xz ay-2ab+2by-y² ay²+2a²-a³-2y² a²+ab+ax+bx 6m-12-2n+mn x+y-x²-xy 4ab²+5ab+a РАЗЛОЖИТЕ НА МНОЖИТЕЛИ

M³-m-am²+a x²+4yz-xy-4xz ay-2ab+2by-y² ay²+2a²-a³-2y² a²+ab+ax+bx 6m-12-2n+mn x+y-x²-xy 4ab²+5ab+a РАЗЛОЖИТЕ НА МНОЖИТЕЛИ
Гость
Ответ(ы) на вопрос:
Гость
[latex] m( m^{2}-1)-a(m^{2}-1); (m^{2}-1)(m-a);(m-1)(m+1)(m-a);[/latex] [latex]x(x-y)+4z(y-x);x(x-y)-4z(x-y);(x-y)(x-4z);[/latex] [latex] y^{2}(a-2)- a^{2}(a-2)=(a-2)( y^{2}-a^{2})=(a-2)(y-a)(y+a);[/latex] [latex]a(a+b)+x(a+b)=(a+b)(a+x)[/latex] [latex]6(m-2)-n(2-m)=6(m-2)+n(m-2)=(m-2)(6+n)[/latex] [latex](x+y)-x(x+y)=(x+y)(1-x)[/latex] [latex]a(4 b^{2}+5b+1) [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы